Role of Spraying Biostimulators Agazone and Atonik for Improvement of Storage Ability of Egg Plant (Solanum melongen L.) Hybrids: Jawaher and Barcelona - Taain, Dhia Ahmed; Salman, Iman Jarry (Research Advances and Challenges in Agricultural Sciences Vol. 6, 2024)
The present study was conducted by using biostimulators, especially agazone and atonik, in improving storage ability of eggplant fruits hybrids of Jawaher and Barcelona. The new orientation in agriculture is to move away from the use of chemical fertilizers, chemical growth regulators and pesticides of different kinds and composition, because of their toxic effects on human and animal organisms. The experiment was conducted in one of the greenhouses of the Agricultural Research Station, College of Agriculture, University of Basrah, during the growing season 2017-2018 in order to improve the storage behavior of eggplant fruits hybrids Jawaher and Barcelona. Agazone. Solutions of agazone with three concentrations (0, 1.5 and 3) ml L-1, and atonik with three concentrations (0, 0.5 and 1) ml L-1 were prepared and the plants were sprayed in the early morning four times. Fruit firmness determined by using fruit pressure instrument, the weight loss was calculated as a percentages, Vitamin C determined according to A.O.A.C. Results indicated that the percentage of weight loss and the percentage of total soluble solids increased while the fruit firmness and the amount of vitamin C decreased with an increment of storage periods. The lowest percentages of the weight loss and the highest percentage of total soluble solids were in fruits treated with 3 ml L-1 agazone. Barcelona fruits gave the highest fruit firmness, vitamin C, total soluble solids and the lowest percentage of weight loss compared to Jawaher fruits, so the study recommended that spraying eggplant plants with agazone at a concentration of 3 3 ml L-1and atonik at a concentration of 1 ml L-1 for four times to improve the qualitative characteristics of the fruits when stored at 13°C for two weeks. Barcelona fruits gave the highest fruit firmness, vitamin C, total soluble solids and lowest percentage of weight loss compared to Jawaher during the two-week storage period, so for the purpose of organizing the display of the crop in the markets, it could be recommended for planting in unheated plastic house under the conditions of south of Iraq.